PERMASALAHAN-PERMASALAHAN REKRUITMEN PENDIDIKAN DAN KEPENDIDIKAN - Hariza Putra, Naufal; Neftihana, Neftihana; Aini Fadila, Nurul; Ananda, Rizki (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Recruitment of educators and education personnel in basic education plays an important role in ensuring the availability of quality human resources at this level. The aim of the recruitment process is to attract individuals who have the necessary qualifications, skills and motivation to excel as educators in the basic education environment. This includes the careful selection of teachers, principals, administrative staff and other support personnel based on factors such as their academic and professional qualifications, ability to facilitate learning, involvement in school committees and understanding of diversity. By implementing a comprehensive and sustainable recruitment strategy for educators and educational staff in the basic education field, we aim to meet the need for qualified professionals, improve the quality of education, and foster an inclusive and diverse learning environment.